Financial literacy as a tool for women entrepreneur empowerment: perspectives from state creditors - Noraizan Ripain; Ag. Kaifah Riyard Kiflee; Sharifah Milda Amirul; Nur Shahida Ab Fatah; Lee, Andy Chen Hiung; Rasid Mail (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2024)
Empowering women entrepreneurs with financial literacy knowledge is vital to ensure their sustainability in the competitive business environment. It is indisputable that women entrepreneurs who possess strong financial literacy will gain significant benefits. In Sabah, government agencies offer various support initiatives, including funding and loan programs, to support the women entrepreneurs in the region. However, many women entrepreneurs face challenges that relate to financial literacy, which can limit their ability to access these funds or manage business finances effectively. Thus, this study aims to explore the challenges faced by the women entrepreneurs in Sabah in managing their loan. Additionally, this study also intends to examine the state creditors initiative from a financial literacy perspective in effort to assist women entrepreneurs in Sabah. By highlighting the critical importance of financial literacy among the women entrepreneurs, this research contributes to the ongoing discussions on women's empowerment and the survival in sustaining their business practices.